Topiramate for the Treatment of Hypnic Headache: A Case Report, Including Polysomnography - Meliha Tan; Sibel Karaca; Başak Karakurum Göksel; Mehmet Ali Habeşoğlu (Türk Nöroloji Dergisi, 2009)
Hypnic headache is a primary, rare headache disorder of the elderly, which occurs during sleep. Polysomnography (PSG) studies have shown that hypnic headache occurs with much gretaer frequency during REM sleep than during non-REM sleep. We present a 69-year-old male that had been waking from sleep due to headaches that have occurred every night for 10 years and was diagnosed as hypnic headache according to International Headache Society (IHS) criterion. He did not benefit from lithium treatment. After taking topiramate 100 mg/day his headaches disappeared. PSG recordings made while he was taking topiramate showed that he had no headaches. He discontinued topiramate on his own and his headaches returned. Subsequently, three weeks after he stopped taking topiramate, two hypnic attacks were recorded during a second PSG-1 during REM and 1 during non-REM sleep. In two records, both the duration of REM and non-REM sleep were reduced. PSG while the patient was taking topiramate showed a higher proportion of REM sleep and fewer awakenings than did the second PSG. Our findings support the view that hypnic headache attacks arise directly from sleep, not from sleep stages. Changes in sleep physiology in the elderly may contribute to hypnic headache. Topiramate may be an effective alternative treatment for hypnic headache in cases unresponsive to lithium or in those that experience intolerable side-effects